EFEKTIVITAS MODEL GALLERY WALK TERHADAP AKTIVITAS DAN KETERAMPILAN MENULIS PANTUN SISWA KELAS V SD NEGERI 59 GAROTIN KECAMATAN ANGGERAJA KABUPATEN ENREKANG - Iyyut Hajrianti Mandrasari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the effectiveness of implementing Gallery Walk model on the learning activities and skills in writing pantun of the fifth grade students at SD Negeri 59 Garotin, Kecamatan Anggeraja, Kabupaten Enrekang. The type of experimental research used in this study was Quasi Experimental Research with Non-Equivalent Control Group Design. The students’ learning outcomes were analyzed by using t test after the prerequisite test was carried out, namely: the normality test and the homogeneity test.. The results showed that the average percentage of the students' learning activities in the experimental class was 91.06% which was included in the very high category while the average percentage in the control class was 76.78%. The results also showed that the average value of the students’ learning outcomes in the experimental class was 87.36%, while the average value in the control class was 77.05%. in addition, the result of t test revealed that the value of tcount (2.875) > ttable (2.032) with Sig (2-tailed) < 0.05, namely 0.007. Thus, the hypothesis was proven to be accepted.